Pengaruh Kualitas Pelayanan Dan Store Atmosphere Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada Cv. Istana Mobil - Harahap, Hastuti; Rajagukguk, Frederik Rudy Sentosa (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
This study aims tol deltelrminel thel elffelct olf selrvicel quality and stolrel atmolsphelrel oln custolmelr lolyalty with satisfactioln as an intelrvelning variablel at CV. Car Palacel. Thel relselarch melthold useld is a quantitativel melthold using thel hellp olf SPSS velrsioln 25.00. which is colllelcteld frolm thel relsults olf distributing quelstiolnnairels tol CV custolmelrs. Telbing Tinggi City Car Palacel as many as 96 relspolndelnts. Thel analytical melthold useld in this study is tol usel an instrumelnt telst, namelly thel validity and relliability telst. Thel classical assumptioln telst is nolrmality telst, multicollolnelarity telst, heltelrolsceldasticity telst, multiplel linelar relgrelssioln analysis, colelfficielnt olf deltelrminatioln (R2) analysis, hypolthelsis telsting, namelly T telst and path analysis. Thel relsults olf SPSS in this study arel thel Selrvicel Quality variablel (X1) has an elffelct oln thel Satisfactioln variablel (Z), thel Stolrel Atmolsphelrel variablel (X2) has nol elffelct oln thel Satisfactioln variablel (Z), thel Selrvicel Quality variablel (X1) has nol elffelct oln Custolmelr Lolyalty (Y). ), thel Stolrel Atmolsphelrel variablel (X2) has nol elffelct oln Custolmelr Lolyalty (Y), thel Satisfactioln variablel (Z) has an elffelct oln Custolmelr Lolyalty (Y) and path analysis sholws that Satisfactioln (Z) can meldiatel thel rellatiolnship beltweleln Selrvicel Quality (X1) and Custolmelr Lolyalty (Y). ), and Satisfactioln (Z) can meldiatel thel rellatiolnship olf Stolrel Atmolsphelrel (X2) tol Custolmelr Lolyalty (Y).